Dulcina: a new variety of sweet sorghum for Tamaulipas and central Nuevo León - Williams-Alanís, Héctor; Aranda-Lara, Ulises; Árcos-Cavazos, Gerardo; Zavala-Garcia, Francisco; Rodríguez-Vázquez, María del Carmen; Elizondo-Barrón, Jorge (Revista Mexicana de Ciencias Agrícolas, 2025)
Sweet sorghum is an excellent potential source for bioethanol production due to its hardiness, tolerance to drought and high temperatures and adaptation to marginal regions. It provides renewable energy capable of supplanting fossil fuels. Crosses between contrasting genotypes were made at the Marín Campus of the Faculty of Agronomy of the Autonomous University of Nuevo León during the autumn-winter 2009-2010 cycle. Dulcina originated from the cross of SBB-25 x Rox Orange, which was subjected to the method of furrow per panicle or pedigree from the F2 generation for four generations. The selection (SBB-25 x Rox Orange) 17-1-1-1 was registered with the CNVV on January 21, 2021, under the name Dulcina. It adapted favorably in central Nuevo León and Tamaulipas. The panicles are compact, with small grains, orange in color, of intermediate cycle (74.4 to 87.1 days to flowering), with a bioethanol production between 2 614 to 3 925 L ha-1, higher than the best control by 6.1 to 32.3%, equivalent to 191 to 959 L ha-1. It also had tall plants (221 to 235 cm) and a sugar content of 16.4 to 20.4 °Brix. In southern Tamaulipas, Dulcina was more tolerant of lodging than Keller and RB-Cañero. It was tolerant to leaf blight [Helminthosporium turcicum (Pass.) Leo and Suggs] and anthracnose [Colletotrichum graminicola (G.E. Wilson)] and was superior (p≤ 0.05) to Keller.
Keywords: bioethanol production; brix; sweet sorghum